Perbandingan Komposisi dan Struktur Komunitas Makroalga antara Pulau Semak Daun dan Pulau Pramuka di Taman Nasional Kepulauan Seribu, DKI Jakarta: Comparison of Macroalgae Community Composition and Structure between Semak Daun Island and Pramuka Island in Kepulauan Seribu National Park, DKI Jakarta - Fadhillah, Hilwa Syifa; Setia, Tatang Mitra; Kusumahadi, Khoe Susanto; Handayani, Sri (Departemen Biologi, Institut Pertanian Bogor, 2024)
Kepulauan Seribu have diverse biodiversity, one of which is macroalgae located in the Tourism Utilization Zone and the residential zone. Environmental factors, such as substrate, water quality and the presence of human activities, are very different on each island. The purpose of this study was to determine the differences in the composition and structure of macroalgae communities on islands in the Tourism Utilization Zone, Semak Daun Island and islands in the Settlement Zone, Pramuka Island. Settlement Zone, Pramuka Island. The method used is a quadrat transect. 16 types of macroalgae were found on Semak Daun Island and 26 types of macroalgae on Pramuka Island. The diversity value on Semak Daun Island is categorized as moderate with a value of 1.84 and on Pramuka Island is categorized as moderate with a value of 2.64. The highest INP value on Semak Daun Island is Sargassum binderi and the highest INP on Pramuka Island is Halimeda macroloba.